Effectiveness of Village Fund Allocation Management (Add) in Loce Village, East Sahu District, West Halmahera Regency in 2017-2020 - Noverita Lamo; Hikmahwati; Julkawait (Indonesian Journal of Applied Accounting and Finance, 2022)
This study aims to determine the effectiveness of the management of Village Fund Allocation (ADD) in Loce Village, East Sahu District, West Halmahera Regency in 2017-2020. The type of research used is qualitative research with a descriptive approach with data collection methods through interviews and documentation. The results showed that village financial management in the Loce Village Government has carried out management activities, namely planning, implementation, administration, reporting, and accountability activities based on the guidelines of the Minister of Home Affairs Regulation Number 20 of 2018. The overall level of effectiveness of village fund allocation management in 2017-2020 was in the effective category. The level of effectiveness in 2017 and 2018 was 100%, in 2019 it was 93%, and in 2020 it was 99%